2x^2=11x+40

Simple and best practice solution for 2x^2=11x+40 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x^2=11x+40 equation:


Simplifying
2x2 = 11x + 40

Reorder the terms:
2x2 = 40 + 11x

Solving
2x2 = 40 + 11x

Solving for variable 'x'.

Reorder the terms:
-40 + -11x + 2x2 = 40 + 11x + -40 + -11x

Reorder the terms:
-40 + -11x + 2x2 = 40 + -40 + 11x + -11x

Combine like terms: 40 + -40 = 0
-40 + -11x + 2x2 = 0 + 11x + -11x
-40 + -11x + 2x2 = 11x + -11x

Combine like terms: 11x + -11x = 0
-40 + -11x + 2x2 = 0

Factor a trinomial.
(-5 + -2x)(8 + -1x) = 0

Subproblem 1

Set the factor '(-5 + -2x)' equal to zero and attempt to solve: Simplifying -5 + -2x = 0 Solving -5 + -2x = 0 Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -2x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + -2x = 0 + 5 -2x = 0 + 5 Combine like terms: 0 + 5 = 5 -2x = 5 Divide each side by '-2'. x = -2.5 Simplifying x = -2.5

Subproblem 2

Set the factor '(8 + -1x)' equal to zero and attempt to solve: Simplifying 8 + -1x = 0 Solving 8 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-8' to each side of the equation. 8 + -8 + -1x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -1x = 0 + -8 -1x = 0 + -8 Combine like terms: 0 + -8 = -8 -1x = -8 Divide each side by '-1'. x = 8 Simplifying x = 8

Solution

x = {-2.5, 8}

 

See similar equations:

| 16k-3(k+5)=48 | | 7(w-1)-5=-2(-5w+1)-9w | | x^2=245 | | 16=d-12-14 | | -2(3x-1)=4x | | 16x-28h=x | | 6x+4(x+8)=102 | | 8(s+3)=6(s-6) | | 2x-3=2(x-2) | | x(5x+4)=2x^2-7x+4 | | 3(x-23)+3(x-4)=33 | | g-5+3=-13 | | -2(4v-7)+5v=6+2(6v-5) | | 4w-2(1-w)=38 | | y=-6*-5+5 | | 24k^2+24k=0 | | 7y+4-3y=24 | | 5x-6=z | | 3y^2+15y+18=0 | | 4b+8-12=10 | | (5x-18)-4=-36 | | 9(z+4)-3(z-4)=3(z-4)+2(z-4) | | 6y+1-3(-2y-1)=2(y-4) | | 4b-16=2b+8 | | 4(v+8)=-3(4v-8)+6v | | x(5x+12)=2x^2-4x+64 | | 3p-7q=4 | | -8y=-9x+3 | | 0.3x-8=-2 | | 2a-1=3a+12 | | 0+-5=5 | | 4+17u=175 | | 5xn= | | 15-4n=-13 | | x^2-64=7 | | x^3-3x^2-5x+15=0 | | 7xn= | | 5x^2-2x-4=0 | | 5x^2+4=24 | | 5(x-5)-9=-6(-3x+5)-7x | | v^2+25v-3750=0 | | 11j-88=13.2 | | -3+9b=36 | | n+21= | | 6x-57=23 | | 6x-5y=23 | | x-12=5x+28 | | 4-3x=23 | | n-10= | | 3+11x=80 | | -3(4y-3)+4y=3+3(2y-4) | | 25x^2+4=15 | | 189=-1k+10 | | 2a=6a+12 | | 9x+15+6x+15= | | -20+8b=3b | | 3(v-1)=3v+3-2(-7v-5) | | X-2y=11 | | 2x-2=3x*6 | | (3x^3-18x^2)(-2x+12)=0 | | x^2+36=7 | | 1250-113= | | 2x=18+2y | | 7(v+4)=-4(2v-9)+9v | | 8x=12x-20 |